Fiber sensor based on Fabry‐Perot/Mach‐Zehnder hybrid interferometer for transverse load and temperature. Issue 2 (12th September 2020) - Han, Yang; Liu, Bo; Wu, Yongfeng; Mao, Yaya; Zhao, Lilong; Sun, Tingting; Nan, Tong; Wang, Jin; Tang, Rong
Abstract: A fiber optic sensor based on array of silica microspheres and air cavity have been fabricated in fusion splicer and experimentally demonstrated in this article. The four‐microspheres structure stimulates higher‐order cladding modes of the gaussian beam, and the air cavity acts as a coupler for Mach‐Zehnder interferometer (MZI) on the one hand and a Fabry‐Perot interferometer (FPI) on the other. The sensing head is subjected to temperature and transverse load where the sensitivity of 160 pm/°C and 124.6 pm/N are obtained, respectively. Compared with similar sensors, the sensor has the advantages of high sensitivity, low‐cost and practical, and it will have a great market prospect.